Portland Cement Use in Dental Root Perforations: A Long Term Followup - Álvaro Henrique Borges; Matheus Coelho Bandeca; Mateus Rodrigues Tonetto; Luis Augusto Faitaroni; Elibel Reginna de Siqueira Carvalho; Juliane Maria Guerreiro-Tanomaru; Mário Tanomaru Filho (Case Reports in Dentistry)
Root canal and furcal perforations are causes of endodontic therapy failure and different materials that stimulate tissue mineralization have been proposed for perforation treatment. In the first case, a patient presented tooth 46 with unsatisfactory endodontic treatment and a periapical radiographic lesion. A radiolucent area compatible with a perforating internal resorption cavity was found in the mesial root. The granulation tissue was removed, and root canals were prepared. The intracanal medication was composed of calcium hydroxide and the perforation cavity was filled with Portland cement. The 11-year followup showed radiographic repair of the tissue adjacent to the perforation and absence of clinical signs and symptoms or periapical lesion. In the second case, a patient presented with edema on the buccal surface of tooth 46. The examination showed a radiolucent area in the furcation region compatible with an iatrogenic perforation cavity. The mesial root canals were calcified, and only the distal root canal was prepared. The cavity was filled with a calcium hydroxide-based paste and the distal root canal was obturated. In sequence, the perforation cavity was filled with Portland cement. The 9-year followup showed the tooth in masticatory function with radiographic and clinical aspects compatible with normality.